2018
DOI: 10.1007/s00359-018-1288-7
|View full text |Cite
|
Sign up to set email alerts
|

Response of rainbow trout’s (Oncorhynchus mykiss) hypothalamus to glucose and oleate assessed through transcription factors BSX, ChREBP, CREB, and FoxO1

Abstract: We aimed to obtain information regarding mechanisms that link glucose- and fatty acid-sensing systems to expression of neuropeptides that regulate food intake in the fish brain. We assessed the relative expression and protein levels of the transcription factors BSX, ChREBP, FoxO1, and CREB in the hypothalamus of rainbow trout (Oncorhynchus mykiss) treated for 6 h with either glucose or oleate in vivo (intra-cerebroventricular treatment with 1 µl 100 g body weight of 40 µg glucose or 1 µmol oleate) or in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 58 publications
3
12
0
Order By: Relevance
“…Accordingly, in rainbow trout the phosphorylation status and mRNA abundance of CREB decreased in the hypothalamus and hindbrain after treatment with CCK-8 and GLP-1. This situation is comparable to that observed in mammals under food deprivation (Ren et al 2013) and in fish under anorexigenic conditions such as those elicited by oleate ICV treatment (Conde-Sieira et al 2018). Nevertheless, the phosphorylation status (hypothalamus) and mRNA abundance of FoxO1 (hypothalamus and hindbrain) increased after treatment with CCK-8 and GLP-1.…”
Section: Cck-8 and Glp-1 Treatment Elicit Changes In Integrative Pathsupporting
confidence: 80%
See 2 more Smart Citations
“…Accordingly, in rainbow trout the phosphorylation status and mRNA abundance of CREB decreased in the hypothalamus and hindbrain after treatment with CCK-8 and GLP-1. This situation is comparable to that observed in mammals under food deprivation (Ren et al 2013) and in fish under anorexigenic conditions such as those elicited by oleate ICV treatment (Conde-Sieira et al 2018). Nevertheless, the phosphorylation status (hypothalamus) and mRNA abundance of FoxO1 (hypothalamus and hindbrain) increased after treatment with CCK-8 and GLP-1.…”
Section: Cck-8 and Glp-1 Treatment Elicit Changes In Integrative Pathsupporting
confidence: 80%
“…Hypothalamus protein lysates (10 μg) were used for Western blot with antibodies from (1) Cell Signaling Technology: anti-phospho AMPKα (Thr172) reference #2531, anti-AMPKα reference #2532, anti-phospho CREB (Ser133) reference #9198, anti-CREB reference #9197, anti-phospho-FoxO1 (Thr24) reference #9464, anti-FoxO1 reference #9454, anti-phospho mTOR (Ser2448) reference #5536 and anti-β-tubulin reference #2146; (2) Sigma: anti-mTOR reference #T2949; (3) Abcam: anti-BSX reference #56092. All these antibodies cross-react successfully with rainbow trout proteins of interest (Skiba-Cassy et al 2009, Kamalam et al 2012, Velasco et al 2016a, Conde-Sieira et al 2018. After washing, membranes were incubated with an IgG-HRP secondary antibody reference #2015718 (Abcam) and bands were quantified by Image Lab software version 5.2.1 (BIO-RAD) in a Chemidoc Touch imaging system (BIO-RAD).…”
Section: Western Blotmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study showed that the expression of chrebp was induced in blunt snout bream in response to high dietary levels of carbohydrate (19) . Another study reported that the increased expression of chrebp enhanced the expression of target genes involved in glycolysis, glycogen storage and lipogenesis (60) . In the present study, the up-regulated expression of srebp1 (3 and 6 h), chrebp (6 h), acc (6 h), fas (1, 3 and 6 h) in the livers of grass carp following the oral administration of starch indicated that the process of lipogenesis had been activated.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of nutrient-sensing systems leads to the activation of mammalian target of rapamycin (mTOR) and the inhibition of AMP-activated protein kinase (AMPK), which in turn modulate the transcription factors forkhead box protein O1 (FOXO1), cAMP response element binding protein (CREB) and brain homeobox transcription factor (BSX). Such transcription factors produce changes in the abundance of neuropeptides, as demonstrated in mammals (Blanco Martínez de Morentin et al, 2011;Diéguez et al, 2011;Gao et al, 2013) and fish (Conde-Sieira et al, 2018;Dai et al, 2014;Librán-Pérez et al, 2015b;Otero-Rodiño et al, 2017).…”
Section: Introductionmentioning
confidence: 94%